Green Finance and Its Influence on Environmental Quality in Indian Firms - Kumar C (Journal of Informatics Education and Research, 2025)
This study examines how green finance affects environmental quality during the period 2015 to 2025 in Indian companies. The impact of green finance on an individual company’s environmental performance will be studied in this analysis, assuming the green innovation, size, leverage, governance and other characteristics of the company to be taken in to account. Evidence of positive green finance impact on environmental performance has been established through the use of fixed effects estimation, meaning more green finance will be associated with improved performance in the environment. Evidence described in the analysis and the graphical presentation sequentially in the decade demonstrates an increase in green finance and environmental performance, suggesting the overall increase in corporate environmental responsibility in the country India. These results indicate the importance of green financing. The findings provide backing to strengthen India’s green finance ecosystem through policies focused on regulatory incentives and disclosure requirements. This research connects sustainability in finance to environment outcomes, focusing on the literature on the sustainability of finance, environment governance at the firm level, and climate-aligned growth in emerging markets. The paper states the increased reach of green finance in India will provide the country the opportunity to transform to a corporate climate, low on carbon, resource efficient resilient to climate change and environment, and will support India’s achievement of the UN SDGs 12 and 13.